2021
DOI: 10.5489/cuaj.7474
|View full text |Cite
|
Sign up to set email alerts
|

A population-based retrospective cohort study analyzing contemporary trends in the surgical management of urinary stone disease in adults

Abstract: Introduction: We aimed to review the trends and incidence of surgical intervention for adults with upper urinary tract stones in Ontario, Canada, and to hypothesize potential causes for the observed changes. Methods: We carried out a retrospective, population-based cohort study using administrative databases held at the Institute of Clinical Evaluative Sciences (IC/ES) to identify all adults (≥18 years) who underwent surgical treatment for urolithiasis, defined by records using a combination of both hospital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The reported incidence of urolithiasis in males is estimated to be two-fold higher than females, 11 but recent data has shown a narrowing of the gender gap. 7,8 In our study we investigated the effect of gender on the presentation and outcome of patients visiting the ED, that were found to have ureteral stones on CT. We report in our study that female presentation at the ED with ureteral stones was associated with elevated body temperature, pulse rate, nausea, vomiting elevated serum CRP, and a higher incidence of positive urine cultures. Males admitted were found to have increased serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported incidence of urolithiasis in males is estimated to be two-fold higher than females, 11 but recent data has shown a narrowing of the gender gap. 7,8 In our study we investigated the effect of gender on the presentation and outcome of patients visiting the ED, that were found to have ureteral stones on CT. We report in our study that female presentation at the ED with ureteral stones was associated with elevated body temperature, pulse rate, nausea, vomiting elevated serum CRP, and a higher incidence of positive urine cultures. Males admitted were found to have increased serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…4 Males have a two-fold higher incidence of urolithiasis than females, 5,6 although, recent studies reported a narrowing of the gender gap. 7,8…”
Section: Introductionmentioning
confidence: 99%
“…4 Males have an estimated two-fold higher incidence of urinary calculi than females, 5 although recent data has shown a decrease in this reported difference between males and females. 6,7 The incidence of renal colic has been reported to increase in the different age groups, as reported in a study by Fwu et al 4 In their study they investigated ED visits due to renal colic, over a 17-year period.…”
Section: Introductionmentioning
confidence: 92%
“…They noted an increase in ED admission rates in each age group. A recent study from Ontario, Canada, 6 reported that between the years 2002 and 2019, for every increase by 1% in the population size, there was a 2.6% rise in stone related surgical procedures.…”
Section: Effect Of Age On Presentation and Outcome In Renal Colicmentioning
confidence: 99%
“…Most of KSD patients (or stone formers) are asymptomatic and may require no specific treatment [2] , [3] . In complicated KSD, extracorporeal shock wave lithotripsy (ESWL), percutaneous nephrolithotomy (PNL), ureteroscopy (URS) and other surgical procedures are the common therapeutic procedures to remove kidney stones [4] , [5] , [6] . Nevertheless, there is a high recurrence rate following the stone removal [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%